Analisis Sistem Program One Student One Client Pendampingan Ibu Hamil oleh Mahasiswa Keperawatan di Kota Semarang - Mukhamad Musta'in; Sri Achadi Nugraheni; Untung Sujianto (Jurnal Manajemen Kesehatan Indonesia, 2017)
Maternal mortality rate (MMR) and infant mortality rate (IMR) are one of the main indicators of a country's health status. MMR in Semarang was increasing since 2013 (107.95 per 100,000 live birth) become (128.05 per 100,000 live birth) in 2015. Various efforts have been made to handle the increase in maternal mortality rate in Semarang, one of them is OSOC program to accompany pregnant women. However, its implementation has not run optimally and encounters several obstacles. The purpose of the research was to analyze the input, process, and output aspects of the One Student One Client Program to accompany  pregnant women by Nursing Students in Semarang. This was qualitative research with descriptive explorative approach through in-depth interview and focus of group discussion. The main informants were; Head of Health Section of Central Java Provincial Health Office and triangulation informant; 2 Heads of Public health services and 2 nurses / midwife coordinator, 2 Head of study program, 2 field supervisors, 14 nursing students and 7 pregnant women / postpartum. Data processed and analysed by content analysis method.  The result showed that the input aspect: which was human resources, had been sufficient, but insufficient in funds, infrastructure facilities only in the form of modules, the policy had not been written and  there was no memorandum of understanding / MoU between the health office and educational institutions.